Effectiveness of Life Review Therapy on Quality of Life in the Late Life at Day Care Centers of Shiraz, Iran: A Randomized Controlled Trial - Farkhondeh Sharif; Iran Jahanbin; Afsar Amirsadat; Mahboobeh Hosseini Moghadam (Shiraz University of Medical Sciences, 2018)
Background: Life review therapy, used as part of a comprehensive therapy plan for increasing the quality of life of the elderly, helps them to resolve their past conflicts, reconstruct their life stories, and accept their present conditions. The present study aimed to explore the effectiveness of life review therapy on the quality of life of the elderly. Methods: The present study was a randomized controlled trial with a pre-posttest design during April to Aug 2014. The study was conducted on 35 members of the elderly day care centers in Shiraz, Iran, that were randomly assigned to two groups (experimental and control). The subjects in the experimental group attended 8 two-hour sessions of life review therapy. The quality of life of the elderly participants was evaluated before, immediately, one month, and three months after the intervention using the quality of life questionnaire (WHOQOL_BREF). Data analysis was conducted through SPSS version 22, using statistical tests including Chi-square, repeated measures test and T-test, with the significance level of 0.05. Results: The results of the study showed that life review therapy interventions significantly improved the quality of life of the elderly (P<0.05). Moreover, group interaction with passage of time was also significant, which indicates that the pattern of changes has been different between the two groups. Conclusion: The findings of the study confirm the research hypotheses, showing that the application of life review is effective and viable. It is recommended that all nursing homes and even the families of the elderly should employ this convenient, inexpensive, quick, and practical method. Trial Registration Number: IRCT2015021621106N1